Implementasi Media Pembelajaran (PUGAWA) Untuk Meningkatkan Minat Belajar Bahasa Indonesia Siswa Kelas VII SMPN 2 Jenangan Ponorogo - Shaila Rahma Anggraini; Fauzatul Ma’rufah Rohmanurmeta; Sri Bintarti (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
The education system, which is actually used to improve students' abilities to be more active and proficient in learning, is often considered inappropriate and not in accordance with the real situation at school. Students who tend to be shy and passive will not ask or learn on their own what is ordered by the teacher. In addition, lessons that are considered difficult and boring will make students less interested in learning these lessons. One effort to change students' attitudes in learning Indonesian is to use interactive and non-monotonous learning media. Learning media